Fluctuation paths and controversial issues of fiscal policy: Where do these leave us? - Leonardo V. Vera (Romanian Journal of Fiscal Policy (RJFP), 2016)
Main changes have occurred in the comprehension and practice of fiscal policy over the last century. In this paper we do a brief historical account and show that the prominence of fiscal policy as a policy tool has waxed and waned, a condition that has hindered the capability of researchers to come to firm conclusions regarding the stabilization properties and impacts of it. Against this backdrop, we discuss and evaluate the several arguments on the impact of fiscal policy on output, inflation and the external accounts and also examine the very popular sustainability framework focusing on interactions and feedbacks among policy and endogenous variables affecting debt ratios. We conclude that there are good reasons to think that the potential usefulness of fiscal stabilization needs to be re-considered.
Keywords: H3; H6; H60; 330; Fiscal Policy; anti-cyclical fiscal policy; fiscal deficits; twin deficits; fiscal multipliers; sustainability